HIGH SPEED CIRCUIT BREAKER COMPRISING A MOVABLE MAGNETIC SHIM IN AN AIR GAP OF A MAGNETIC CIRCUIT - GAVID, Aurel; BATISTA, Emmanuel; VERNIER, Jean-Pierre; QUENTIN, Nicolas (2025)
A circuit breaker comprising:- a chassis, a first contact (14), and a second contact (16),- an actuator mechanism (18) movable between a closed position, and a tripped position,- a tripping system (22) comprising a magnetic circuit (44) surrounding the first contact and delimiting a first air-gap, and a core (46) at least partly located in the first air gap and subject to a magnetic force (F2), the tripping system being adapted for preventing the actuator mechanism from switching from the closed position to the tripped position as long a current in the contacts does not exceed a threshold,- a setting system (24) for setting the threshold.The magnetic circuit defines a second air-gap, the setting system comprising a magnetic shim (64) movable with respect to the magnetic circuit between a plurality of positions in which the shim is at least partly located in the second air-gap.